Relationship between Sports and Self-Esteem among University Students - Dev, Smitha; Uthaman, Neena (International Journal of Psychosocial Rehabilitation, 2020)
This study explores the relationship between positive self-esteem and sports participation among adolescent students. One of the most prominent extracurricular activities is sports. It will teach about teamwork and also boost self-esteem among the students. This data was collected from a sample of 319 sports participant’s and non-participant’s students in the age range of 15–27 and above. The survey varied from freshmen’s to senior students of different universities all over the Emirates of Abu Dhabi. The participants were requested to reply to a series of statements on the self-esteem scale, which is an adapted version of the Rosenberg’s self-esteem scale (The Morris Rosenberg Foundation). Higher scores on this variable indicate a higher level of self-esteem. The data were analyzed by using statistical techniques like Spearman Rank correlation to find out the relationship between sports participation and self-esteem. The results showed that there was a significant relationship between self-esteem and sports performance. The participation ratio also showed a significant variation between both the sexes (male & female) in sports activities. Active participation in sports can enhance self-awareness and the level of commitments among the students. Therefore, it should be made mandatory for all the universities across the UAE to give more opportunities for students to develop their sports skills and spirit.